2014
DOI: 10.1177/0194599814521555
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and Risk of Bleeding in Children Undergoing Tonsillectomy

Abstract: In a real-world practice setting, dexamethasone use was associated with a small absolute increased risk of revisits for bleeding. However, the upper bound of this risk increase does not cross published thresholds for a minimal clinically important difference. Given the benefits of dexamethasone in reducing postoperative nausea and vomiting and the larger body of evidence from trials, these results support guideline recommendations for the routine use of dexamethasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…We identified 46 unique database or registry studies or case series with ≥1000 children (reported in multiple papers) addressing PTH. 3,4,123-176…”
Section: Resultsmentioning
confidence: 99%
“…We identified 46 unique database or registry studies or case series with ≥1000 children (reported in multiple papers) addressing PTH. 3,4,123-176…”
Section: Resultsmentioning
confidence: 99%
“…Ondansetron is expensive and prolongs QT interval [9]. Dexamethasone use in certain surgeries is associated with an increased risk of postoperative bleeding [8,38]. Intravenous lidocaine is considered inexpensive and safe, and has been commonly used as an adjuvant for pediatric general anesthesia [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for bleeding complications after TE and ATE have been described, such as male gender [82], [83], [84], [85], [86], [87], [88], [89], [90]. To the best of our knowledge, a different gender-specific and age-related post-tonsillectomy hemorrhage rate has never been described before.…”
Section: Discussionmentioning
confidence: 99%